Analysis of fatal outcome structure in acute poisoning with hypotensive and antiarrhythmic drugs - K. K. Ilyashenko; G. N. Sukhodolova; M. V. Belova; A. Yu. Simonova; M. M. Potskhveriya (Трансплантология (Москва), 2024)
Background. In many countries, there is an increase in the number of poisoning with antihypertensive and antiarrhythmic drugs taken either accidentally or for suicidal purposes. The mortality rate for these poisonings reaches 6.5%.The aim of the study was to analyze the causes of fatal outcomes in patients with acute poisoning with hypotensive and antiarrhythmic drugs.Material and methods. The inpatient medical records (Form No. 003/y), autopsy reports of forensic chemical and forensic histological studies of 80 people who died from acute poisoning with hypotensive and antiarrhythmic drugs at the N.V. Sklifosovsky Research Institute for Emergency Medicine for the period from 2011 to 2020 were analyzed.Results. The age of patients with acute poisoning with antihypertensive and antiarrhythmic drugs ranged from 16 to 94 years, of which 85% of patients were over 60 years old. Women made up 70%. Twenty five patients died in the toxicogenic stage of poisoning, other 55 died in the somatogenic stage. The causes of poisoning were the intake of hypotensive drugs (mainly calcium channel blockers) in 67% of cases, the intake of antiarrhythmic drugs from the group of beta-blockers in 33%. Poisoning on suicidal intent was recorded in 81.2% of cases. The main causes of death in the toxicogenic stage of poisoning were the following (listed in order of decreasing incidence): exotoxic shock, primary cardiotoxic effect, acute cardiovascular insufficiency. The main cause of patient death in the somatogenic stage was pneumonia.Conclusion. Acute poisoning with antihypertensive and antiarrhythmic drugs, in the vast majority of cases, occurs in patients over 60 years of age. Suicidal attempts make the main cause of poisoning. The main cause of death in the toxicogenic stage of poisoning is exotoxic shock, that one in the somatogenic stage is nosocomial pneumonia.